Envoplakin Inhibits Macrophage Polarization by Altering the Inflammatory Tumor Microenvironment of Melanoma Through the RAS / ERK Signaling Pathway - Cai W; Chen M (Dove Medical Press, 2024)
Weilin Cai,1,2 Minliang Chen2 1Medical School of Chinese PLA, Beijing, People's Republic of China; 2Senior Department of Burns and Plastic Surgery, the Fourth Medical Center of PLA General Hospital, Beijing, People's Republic of ChinaCorrespondence: Minliang Chen, Senior Department of Burns and Plastic Surgery, the Fourth Medical Center of PLA General Hospital, No. 51 Fucheng Road, Haidian District, Beijing, 100038, People's Republic of China, Tel/Fax +86-010-66867304, Email minliangchen2022@163.comPurpose: Tumor growth induces the tumor margin to become a transition zone rich in immune cells. EVPL is a potential prognostic biomarker for melanoma. Melanoma is difficult to cure because of its high metastasis, so it is urgent to find effective genes to inhibit tumor progression and regulate tumor microenvironment.Methods: Firstly, differentially expressed genes (DEGs) among normal skin, nevus and melanoma samples in GSE3189 were screened. Bioinformatics was used to further explore the hub genes and enriched pathways closely related to the inflammatory response of DEGs in melanoma. We selected EVPL, which is associated with the Ras/Raf signaling pathway, for in vitro study. CCK-8, colony formation, wound healing, Transwell and flow cytometry assays were respectively used to evaluate the proliferation, migration, invasion, and apoptosis of cancer cells. Enzyme-linked immunosorbent assay was conducted for the monitoring of changes in the tumor microenvironment. To evaluate the effect of EVPL on macrophage recruitment, we established a co-culture system in a Transwell chamber. The polarization of macrophages was examined after treatment of cells with RAS/ERK signaling inhibitors SCH772984 and sh-EVPL. Additionally, changes in the expression of pathway proteins were measured by Western blot.Results: Among the screened hub genes, EVPL was associated with the Ras/Raf pathway, a key signaling pathway in melanoma, and may be involved in regulating the inflammatory microenvironment of melanoma. Oe-EVPL was proved to suppress melanoma cell malignant progression. By inhibiting EVPL expression, the inhibitory effects on melanoma progression induced by the addition of SCH772984 were reversed. Furthermore, EVPL was found to inhibit the expression of chemokines, the recruitment of macrophages, and the polarization of macrophages through the Ras/Raf/ERK signaling pathway.Conclusion: EVPL can inhibit the progression of melanoma through the RAS/ERK signaling pathway, change the inflammatory tumor microenvironment of melanoma, and inhibit the recruitment of macrophages.Keywords: melanoma, inflammatory tumor microenvironment, EVPL, Ras/Raf/ERK signaling pathway, macrophages